Manual de funcionamiento, mantenimiento y aplicación pedagógica de la balanza digital y termómetro infrarrojo láser en el Laboratorio de Investigación de Lácteos de la Carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Masapanta Masapanta, Ana Lucia (2022)
The dairy research laboratory of the Agroindustry major at the Technical University of Cotopaxi has a variety of equipment that facilitates student learning through practices directed by the teachers in charge. This project aimed to implement operation and maintenance manuals for the digital scale and the laser infrared thermometer. Therefore, it was necessary to be guided by background to develop the theoretical framework and the methodology of the manuals where the main characteristics, parts, ignition, requirements, shutdown, mode of operation of the equipment are detailed, and its proper functioning and the different types of maintenance such as routine, preventive and corrective, so that it must be applied according to the requirement, prolonging the useful life of the equipment, it is also essential to consider the security measures for the personnel to give solution to the lack of manuals and provide a helpful guide during the practices, therefore it is crucial to have this type of document. The dairy research laboratory is essential since, through it, the demonstrative practice of the use and operation of the digital scale and the laser infrared thermometer is developed, transforming the theoretical into practice; through the elaboration of passion fruit ice cream, it was possible to demonstrate proper functioning so, the equipment is reliable and easily accessible; all this will be of benefit to the student community of the program, increasing knowledge and skills within the pedagogical, experimental and investigative practices.